Integrating Succession Planning for Family Business Continuity: A Conceptual Analysis - Adebayo, Philips O. (NIU Journal of Social Sciences, 2020)
The economic importance of family business - wealth creation, employment generation, locally rooted and strong connection to their communities cannot be over emphasized; besides being widely acknowledged as major proportion of most small and medium enterprises in the global economy . However, pertinent to most family businesses is the desire to maintain family leadership of the company by appointing as top executive from family members one who has qualification and significant experience with the company. F amily businesses can only position themselves for this and other future expansion by investing in robust managerial development through early involvement of family members and adapting succession planning best practices. This study seeks to advance knowledge on succession planning and managing family businesses by shedding light on the inter-link between them. The study further explained why, despite robust efforts of founderâ€™s investment and commitment, majority of family businesses still failed to survive especially on the transition of such to young generation. From the analysis of this study, the major sources of failure common in family businesses are family conflicts, poor entrepreneurial exposure, incompetent members of the next generation and flamboyant lifestyles among others . The study draws conclusion and make recommendations base on the findings. Keywords: Business transition, Family business, Family conflicts,          Family participation, Succession planning